Prevalence and Reasons for Migration Among Nursing Students - Maryam Khoei Esfahani (Beyhagh)
Background and Aims: The migration of nurses is a dynamic process arising from the changing social conditions that can affect the society at the source. Due to the fact that the process of migration of nurses can be worrying as the main part of the human resources of the health system, this study was conducted with the aim of the prevalence and reasons for the desire to migrate among nursing students. Materials and Methods: This descriptive-analytical study was conducted on 384 nursing students using stratified random sampling from Isfahan and Gonabad University of Medical Sciences in 2019. The data was collected using a researcher-made questionnaire on factors affecting migration. Result: 21.6% of nursing students had very low, 22.1% low, 28.6% moderate, 22.4% high and 5.3% very high tendency to migrate. Inflation, insufficient educational facilities, children's lack of progress, and job discrimination were identified as the main reasons for the desire to migrate. Also, the variables of age, sense of belonging to the homeland, father's bachelor's education and mother's free job are significant predictors of the desire to migrate among nursing students. Conclusion: The results showed that the desire to migrate among nursing students is at an average level. Also,the results of this study led to the identification of factors related to the desire to migrate among nursing students. Therefore, according to the obtained results, it is possible to take an important step towards strengthening the country's health system by formulating comprehensive policies to attract and retain nurses.